Exploring the potential contribution of college bachelor degree programs in Ontario to reducing social inequality. Issue 2 (3rd July 2018) - Skolnik, Michael L.; Wheelahan, Leesa; Moodie, Gavin; Liu, Qin; Adam, Edmund; Simpson, Diane
ABSTRACT: During the past two decades community colleges and technical institutes in several jurisdictions, including parts of Canada, the United States and Australia, have been given the authority to award bachelor degrees. One of the motivations for this addition to the mandate of these institutions is to improve opportunities for bachelor degree attainment among groups that historically have been underserved by universities. This article addresses the equity implications of extending the authority to award baccalaureate degrees to an additional class of institutions in Canada's largest province, Ontario. The article identifies the conditions that need to be met for reforms of this type to impact positively on social mobility and inequality, and it describes the kinds of data that are necessary to determine the extent to which those conditions are met. Based on interviews with students, faculty, and college leaders, it was found that regulatory restrictions on intra-college transfer from sub-baccalaureate to baccalaureate programs and lack of public awareness of a new type of bachelor degree may be limiting the social impact of this reform.